Perancangan User Experience Aplikasi Pemesanan Katering Sekolah Dengan Menggunakan Metode Human-Centered Design - R. P. Hero Wijaya; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The majority of catering currently provide menus in a package and every nutrient and calorie on each package menu has been measured every day. Some katering people don't eat their lunch because one of the factors is not using some food in the package menu that day. This makes students sluggish all day because they do not lack energy for learning activities. By using it, it is necessary to do a new solution that can be used for special users for the right delivery. Mastery of user experience is needed so that the development of the application will get the results of user experience with a good level of success and satisfaction. Human-centered Design (HCD) is an interactive approach that aims to create a system that can be used properly and efficiently. The results of design testing with usability testing get results of 96.39% and the results of evaluation of User Experience Questionnaire (UEQ) on the recording of user experience katering applications get a positive value and get a very good category on aspects of attraction, perspectivity, efficiency, dependence, stimulation and novelty. Thus, it can be concluded that design provides a positive perception in terms of user experience and both in terms of usability.